Erlotinib plus bevacizumab versus erlotinib alone in patients with EGFR-positive advanced non-squamous non-small-cell lung cancer (NEJ026): interim analysis of an open-label, randomised, multicentre, phase 3 trial. Issue 5 (May 2019) - Saito, Haruhiro; Fukuhara, Tatsuro; Furuya, Naoki; Watanabe, Kana; Sugawara, Shunichi; Iwasawa, Shunichiro; Tsunezuka, Yoshio; Yamaguchi, Ou; Okada, Morihito; Yoshimori, Kozo; Nakachi, Ichiro; Gemma, Akihiko; et al.
Summary: Background: Resistance to first-generation or second-generation EGFR tyrosine kinase inhibitor (TKI) monotherapy develops in almost half of patients with EGFR -positive non-small-cell lung cancer (NSCLC) after 1 year of treatment. The JO25567 phase 2 trial comparing erlotinib plus bevacizumab combination therapy with erlotinib monotherapy established the activity and manageable toxicity of erlotinib plus bevacizumab in patients with NSCLC. We did a phase 3 trial to validate the results of the JO25567 study and report here the results from the preplanned interim analysis. Methods: In this prespecified interim analysis of the randomised, open-label, phase 3 NEJ026 trial, we recruited patients with stage IIIB–IV disease or recurrent, cytologically or histologically confirmed non-squamous NSCLC with activating EGFR genomic aberrations from 69 centres across Japan. Eligible patients were at least 20 years old, and had an Eastern Cooperative Oncology Group performance status of 2 or lower, no previous chemotherapy for advanced disease, and one or more measurable lesions based on Response Evaluation Criteria in Solid Tumours (1.1). Patients were randomly assigned (1:1) to receive oral erlotinib 150 mg per day plus intravenous bevacizumab 15 mg/kg once every 21 days, or erlotinib 150 mg per day monotherapy. Randomisation was done by minimisation, stratified by sex, smoking status, clinical stage, and EGFR mutation subtype. The primary endpoint was progression-free survival. This study is ongoing; the data cutoff for this prespecified interim analysis was Sept 21, 2017. Efficacy was analysed in the modified intention-to-treat population, which included all randomly assigned patients who received at least one dose of treatment and had at least one response evaluation. Safety was analysed in all patients who received at least one dose of study drug. The trial is registered with the University Hospital Medical Information Network Clinical Trials Registry, number UMIN000017069. Findings: Between June 3, 2015, and Aug 31, 2016, 228 patients were randomly assigned to receive erlotinib plus bevacizumab (n=114) or erlotinib alone (n=114). 112 patients in each group were evaluable for efficacy, and safety was evaluated in 112 patients in the combination therapy group and 114 in the monotherapy group. Median follow-up was 12·4 months (IQR 7·0–15·7). At the time of interim analysis, median progression-free survival for patients in the erlotinib plus bevacizumab group was 16·9 months (95% CI 14·2–21·0) compared with 13·3 months (11·1–15·3) for patients in the erlotinib group (hazard ratio 0·605, 95% CI 0·417–0·877; p=0·016). 98 (88%) of 112 patients in the erlotinib plus bevacizumab group and 53 (46%) of 114 patients in the erlotinib alone group had grade 3 or worse adverse events. The most common grade 3–4 adverse event was rash (23 [21%] of 112 patients in the erlotinib plus bevacizumab group vs 24 [21%] of 114 patients in the erlotinib alone group). Nine (8%) of 112 patients in the erlotinib plus bevacizumab group and five (4%) of 114 patients in the erlotinib alone group had serious adverse events. The most common serious adverse events were grade 4 neutropenia (two [2%] of 112 patients in the erlotinib plus bevacizumab group) and grade 4 hepatic dysfunction (one [1%] of 112 patients in the erlotinib plus bevacizumab group and one [1%] of 114 patients in the erlotinib alone group). No treatment-related deaths occurred. Interpretation: The results of this interim analysis showed that bevacizumab plus erlotinib combination therapy improves progression-free survival compared with erlotinib alone in patients with EGFR -positive NSCLC. Future studies with longer follow-up, and overall survival and quality-of-life data will be required to further assess the efficacy of this combination in this setting. Funding: Chugai Pharmaceutical.